The Role of Peer Mentors in Promoting Knowledge and Skills Development in Graduate Education. (8th November 2020) - Lorenzetti, Diane L.; Nowell, Lorelli; Jacobsen, Michele; Lorenzetti, Liza; Clancy, Tracey; Freeman, Georgina; Oddone Paolucci, Elizabeth
Abstract : The objective of this study was to explore the role of peer mentorship in facilitating graduate student resiliency, knowledge acquisition, and development of academic competencies. We conducted a qualitative case study, using in-person interview data from sixty-two students recruited from four professional faculties (Education, Medicine, Nursing, and Social Work) at a large Canadian University. We identified four broad themes derived from a thematic and constant comparative analysis of interview data: (1) knowledge sharing, (2) skills development, (3) academic milestones, and (4) program supports. Graduate students reported that peer mentorship promoted the development of learning environments that emphasized community, collaboration, and shared purpose. Students believed that peer mentors facilitated their access to essential procedural and disciplinary knowledge and helped them to develop academic and research skills and achieve key academic milestones. While the majority of the students interviewed had not participated in any formal peer-mentoring program, they recommended that any future program incorporate mentorship training and include access to collaborative spaces and targeted opportunities for students to develop these relationships.